CO-CREATING OPERATIONAL SERVICE EXCELLENCE IN SMES: INTEGRATING ACADEMIC INSIGHTS AND SHARIA BANKING PRACTICES THROUGH SERVICE-DOMINANT LOGIC - Denny Rakhmad Widi Ashari; Gautama Sastra Waskita; Nurani; Ahmad Rifa’i; Muhammad Syahrul Hidayat (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
Small and medium-sized enterprises (SMEs) face increasing pressure to enhance service quality within market uncertainty, limited resources, and rapid digital transformation. However, many SMEs struggle to develop sustainable service excellence due to fragmented capabilities and the absence of structured cross-sector collaboration. This study aims to investigate how co-creation between SMEs, academic institutions, and the banking industry can jointly drive service excellence by adopting the principles of Service-Dominant Logic (SDL). A qualitative exploratory design was employed, using in-depth interviews, expert discussions, and document analysis to examine the interplay of knowledge exchange, resource integration, and collaborative service innovation across the three stakeholder groups. The findings reveal that service excellence emerges through co-created value rather than isolated organizational initiatives. Academic institutions contribute theoretical frameworks and analytical tools, while the banking sector provides financial expertise, risk management practices, and customer service models. SMEs, in turn, integrate these resources to build adaptive capabilities, elevate customer experience, and strengthen operational resilience. The study demonstrates that triadic collaboration enables SMEs to transition toward customer-centric service models, leverage digital technologies, and develop more robust financial and managerial competencies. These insights extend the SDL framework by highlighting the role of multi-actor ecosystems in shaping service innovation within resource-constrained contexts. The implications underscore the need for structured co-creation platforms, capacity-building initiatives, and long-term partnerships to scale SME service excellence. The study further recommends exploring broader ecosystem actors and mixed-method approaches to deepen theoretical and managerial understanding of co-creation-driven service transformation.